Gratification obtained from agricultural information disseminated through radio among Malaysian farmers - Azarian, Zoheir Sabagpour; Hassan, Md. Salleh; Abu Samah, Bahaman (TextRoad Publication, 2012)
Radio is recognized to be the most suitable medium for rural advancement programs. It has potential to be the most effective media in promoting agriculture and development in rural areas, particularly as a tool for the delivery of quick information. A quantitative study was designed to determine how farmers use radio to obtain and gather information to gratify their needs. A total of 400 respondents were selected randomly from four states in Peninsular Malaysia. A multiple linear regression was used to address the research hypothesis. The outcomes of the study are expected to give a deeper understanding of how media help the farmers in meeting their information needs, how they perceive the media, and their beliefs and evaluations of the media programmes.